Verification of the model of the linear-thermoviscolastic behavior of rib-reinforced polyfoams - Yankovskii, Andrey Petrovich (Computational Continuum Mechanics, 2013)
The calculated elastic characteristics of honeycomb structures have been analyzed and compared with the experimental data and the results of calculations obtained by other techniques. It is shown that the proposed model is attractive for practical estimations and can provide valid predictions of the linear – thermoviscolastic behavior of rib-reinforced polyfoams. Creep curves for spatially reinforced honeycomb polyfoams are presented.
Keywords: polyfoam; reinforcement; constitutive relations; structural theory; lightweight filler; ribbed designs; linear viscoelasticity; numerical modeling